Uticaj obrazovanja na društvene promjene / The Impact of Education on Social Change - Forić, Samir; Krčalo, Nezir; Džafić, Adnan (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
We already see a clear difference between the terms education and upbringing in the everyday use of these terms, since one can be educated but not upbrought /nurtured, as well as upbrought /nurtured and uneducated. While education is primarily concerned with human behavior and behavior in the human community and has an intersubjective character, education is related to the degree of knowledge and knowledge of the world within the world of life in which each subject is immersed in his being. The search for knowledge is now being replaced by the search for information and its possession. That is why today's intellectuals are no longer inspired by the search for the secret contained in the fact of our existence, but by collecting and manipulating information on the surface provided by the Internet. Educational institutions are increasingly less a place for acquiring fundamental knowledge that would be at the heart of an individual's view of the world and at the root of his or her life activity.